Development of rotational intraperitoneal pressurized aerosol chemotherapy to enhance drug delivery into the peritoneum - Soo Jin Park; Eun Ji Lee; Hee Su Lee; Junsik Kim; Sunwoo Park; Jiyeon Ham; Jaehee Mun; Haerin Paik; Hyunji Lim; Aeran Seol; Ga Won Yim; Seung-Hyuk Shim; et al. (Taylor & Francis Group, 2021)
This study aims to evaluate the drug distribution, tissue concentrations, penetration depth, pharmacokinetic properties, and toxicities after rotational intraperitoneal pressurized aerosol chemotherapy (RIPAC) in pigs. Because relevant medical devices have not been introduced, we developed our prototype of pressurized intraperitoneal aerosol chemotherapy (PIPAC) and RIPAC by adding a conical pendulum motion device for rotating the nozzle. RIPAC and PIPAC were conducted using 150 ml of 1% methylene blue to evaluate the drug distribution and 3.5 mg of doxorubicin in 50 ml of 0.9% NaCl to evaluate the tissue concentrations and penetration depth, pharmacokinetic properties, and toxicities. All agents were sprayed as aerosols via the nozzle, DreamPen® (Dalim Biotech, Gangwon, South Korea), with a velocity of 5 km/h at a flow rate of 30 ml/min under a pressure of 7 bars, and capnoperitoneum of 12 mmHg was maintained for 30 min. As a result, RIPAC showed a wider distribution and stronger intensity than PIPAC. Compared with PIPAC, RIPAC demonstrated high values of the tissue concentration in the central, right upper, epigastrium, left upper, left lower, right lower, and right flank regions (median, 375.5-2124.9 vs. 161.7-1240 ng/ml; p ≤ .05), and higher values of the depth of concentrated diffusion and depth of maximal diffusion (median, 232.5-392.7 vs. 116.9-240.1 μm; 291.2-551.2 vs. 250.5-362.4 μm; p ≤ .05) in all regions except for bowels. In RIPAC, the pharmacokinetic properties reflected hemodynamic changes during capnoperitoneum, and there were no related toxicities. Conclusively, RIPAC may have the potential to enhance drug delivery into the peritoneum compared to PIPAC.